Study of Teacher Obstacles in Implementing Integrated Thematic Learning Elementary School - Septianda, Swandy (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2021)
This research aims to explore the implementation of integrated thematic learning at SDN 112/1 Muara Bulian. A qualitative approach was used by interviewing eight teachers and observing classroom learning activities. The research results show that the main obstacles in implementing integrated thematic learning include teachers' limited understanding of the principles of Learning Implementation Plans, lack of support and understanding from the school, and the need to increase teachers' abilities in designing learning that suits the characteristics of students. However, this research also found several positive initiatives undertaken by teachers to overcome these challenges, such as training and collaboration between teachers. The novelty of this research lies in its focus on the implementation of integrated thematic learning in elementary schools, especially at SDN 112/1 Muara Bulian, while its implications highlight the need for greater support and more in-depth training for teachers to increase the effectiveness of integrated thematic learning. Therefore, the findings of this research provide an important contribution to the development of teacher professionalism and the development of more effective strategies in improving the quality of learning at the elementary school level.